A Comparative Study on the Notion of Dialogue in Islam and Buddhism - Ramli, Ahmad Faizuddin; Mohamed Ashath,; Ahmad Moghri, (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Interfaith dialogue is a vital tool for promoting understanding and cooperation between different religious communities. This article presents a comparative study of the Islamic and Buddhist perspectives on interfaith dialogue. Drawing on primary sources from both religions, this study explores the theological foundations of interfaith dialogue and the practical strategies employed by Muslims and Buddhists in promoting interfaith understanding. The similarities and differences between the two religions’ approaches to interfaith dialogue are analysed, examining how their respective beliefs, practices, and histories shape their attitudes toward religious diversity. The research design is qualitative using library research by emphasizing content analysis on Islam and Buddhism scripture. The results show that the Islamic paradigm of interreligious dialogue is da‘wah (propagation, invitation or introducing Islam) which is rooted in Tawhid, in contrast, Buddhism promotes liberation from human suffering which is rooted in Bhavana and mindfulness. The study contributes to the principle of interfaith dialogue and provides insights into the potential of interfaith relations for sustaining harmony, peace, and mutual respect in diverse societies. Studies suggest the understanding of each fundamental to encourage Muslim and Buddhist scholars to produce comprehensive interreligious dialogue, theologically and philosophically.